Hukum Adat Di Indonesia Dalam Pandangan Para Ahli Dan Konsep Pemberlakuannya di Indonesia - Arliman, Laurensius (Jurnal Selat, 2018)
Before the VOC came, Indonesia used customary law as a positive law in the archipelago, adhered to and implemented as a custom, hereditary respected by society as a nation tradition. The entry of VOC into Indonesia, foreign society began to pay attention to customary law. At this time the Western Law (Dutch) began to be used although initially only used for the central government area of ââthe Company while for areas that have not mastered can use their customary law or for those who want to submit to Dutch law is allowed. Customary Law is used as a synonym of law not written in legeslative regulation, law living as a convention in state legal bodies (Parliament, Provincial Council and so on), laws arising from judges rulings, living laws as customary rules maintained in the association of life, both in cities and in villages. Customary law conditioned as a solution to legal vacuum is required as a law that is not contrary to legislation. Customary law has the same function and purpose as Indonesias positive law, that is for justice, social control, striving for good as a common goal. The customary law of its existence has been officially recognized by the Indonesian government as agreed by all Indonesian people as one of the official laws. And can be used officially in the community, in addition to the use of laws and regulations made by the government.